Analysis of indoor location and positioning via Wi-Fi signals at FKEKK,UTeM - Ja'afar, Abd Shukur; Hashim, Nik Mohd Zarifie; Awang Md Isa, Azmi; Ali, Nur Alisa; Darsono, Abdul Majid (Engg Journals Publications, 2013)
Global Positioning System (GPS) is widely used as public location and positioning system in navigation of user. However, this application signal is limited, not operational, not available and inefficient for indoor environment. Therefore, the purpose of this project is to analyze indoor location and positioning utilizing the Wi-Fi signals. Wireless position estimation is based on distance measurement in determining the coordinates of user. Scene analysis which called fingerprinting technique is implemented in this project with measurement of received signal strength (RSS) from all the access point. The project has two phases to go through which are the surveying phase and online phase. The unknown location of the target user RSS during online phase will be compare to the database that has been collected during surveying phase. The Euclidean distance algorithm is implemented in calculating the location estimation which the MATLAB software used as the simulation tools. Several analyses have been done to determine the accuracy and effectiveness of the positioning error due to numbers of access point and environment traffic condition.